2021
DOI: 10.14744/semb.2021.92693
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between the Respiratory Severity Score and Extubation Failure in Very-low-birth-weight Premature Infants

Abstract: Objective: The objective of the study is to investigate the utility of the respiratory severity score (RSS), an easy-to-use, non-invasive respiratory failure assessment tool that does not require arterial blood sampling, for predicting extubation failure in very-low-birth-weight premature infants. Methods: Demographic characteristics, clinical course, and neonatal morbidities were retrospectively analyzed. Data were obtained from the files of infants who were admitted t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 36 publications
1
8
0
Order By: Relevance
“…Of these studies, 19 were prospective studies [ 17 , 19 , 23 – 39 ] and the remaining 15 studies were retrospective [ 10 , 16 , 40 52 ], of which seven were multicenter studies [ 16 , 17 , 19 , 23 , 37 , 39 , 49 ] and 27 were single-center studies [ 10 , 24 – 36 , 38 , 40 48 , 50 – 52 ].The sample size ranged from 34 to 926, with the two largest studies including 394 newborns [ 40 ] and 926 newborns [ 17 ], respectively. Three of these studies constructed clinical prediction models [ 16 , 42 , 49 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Of these studies, 19 were prospective studies [ 17 , 19 , 23 – 39 ] and the remaining 15 studies were retrospective [ 10 , 16 , 40 52 ], of which seven were multicenter studies [ 16 , 17 , 19 , 23 , 37 , 39 , 49 ] and 27 were single-center studies [ 10 , 24 – 36 , 38 , 40 48 , 50 – 52 ].The sample size ranged from 34 to 926, with the two largest studies including 394 newborns [ 40 ] and 926 newborns [ 17 ], respectively. Three of these studies constructed clinical prediction models [ 16 , 42 , 49 ].…”
Section: Resultsmentioning
confidence: 99%
“…The main causes of reintubation for EF were frequent apnea, increased respiratory workload, and hypoxemia [ 53 ]. There is evidence that EF is strongly associated with adverse clinical outcomes and mortality [ 10 , 16 , 19 , 40 , 44 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The respiratory severity score is a respiratory index that can evaluate the severity of oxygenation failure and pulmonary status in patients receiving MV, which is calculated by multiplying MAP and FiO 2 , and can be used as an alternative to the oxygenation index, which requires invasive arterial catheterization [ 22 ]. EF patients showed a higher RSS on the first extubation attempt than ES patients [ 8 , 23 , 24 ]. However, this difference was not statistically significant, possibly because of the small number of patients included in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Respiratory severity score is a respiratory index that can evaluate the severity of oxygenation failure and pulmonary status in patients receiving MV, which is calculated by multiplying MAP and FiO2; it can be used as an alternative to oxygenation index (OI), which requires invasive arterial catheterization [17]. EF patients showed a higher RSS at the rst attempt of extubation in the previous studies [8,18,19], and the EF group in this study showed a higher RSS at the rst attempt of extubation than the ES group. However, this difference was not statistically signi cant.…”
Section: Discussionmentioning
confidence: 99%